MiR‐342‐3p promotes osteogenic differentiation via targeting ATF3. Issue 24 (15th November 2018) - Han, Yawei; Zhang, Kun; Hong, Yuheng; Wang, Jingzhao; Liu, Qi; Zhang, Zhen; Xia, Han; Tang, Yutao; Li, Tengshuai; Li, Liandong; Xue, Yuan; Hong, Wei
Abstract : Through their multiple targets, microRNAs (miRNAs) are involved in numerous physiological and pathological processes. In this study, miR‐342‐3p was found to be deregulated with ossification of ligament or osteoporosis. We demonstrate that silencing miR‐342‐3p impairs osteoblast activity and matrix mineralization, while over expression of miR‐342‐3p promotes osteoblast differentiation significantly. Moreover, miR‐342‐3p directly targets activating transcription factor 3 (ATF3), which inhibits transcription of pro‐osteogenic differentiation‐associated genes. In addition, there exists a higher frequency of methylation at the CpG island of the Enah/Vasp‐Like (EVL) locus in undifferentiated pre‐osteoblasts; however, demethylation of the EVL CpG island induces over expression of miR‐342‐3p during osteogenic differentiation. This study suggests that miR‐342‐3p may serves as a potential marker for diagnosis and treatment of ossification of ligament and osteoporosis. Abstract :